2006
DOI: 10.1063/1.2357119
|View full text |Cite
|
Sign up to set email alerts
|

Structural anomalies for a three dimensional isotropic core-softened potential

Abstract: Using molecular dynamics simulations we investigate the structure of a system of particles interacting through a continuous core-softened interparticle potential. We found for the translational order parameter t a local maximum at a density rho(t-max) and a local minimum at rho(t-min)>rho(t-max). Between rho(t-max) and rho(t-min), the t parameter anomalously decreases upon increasing pressure. For the orientational order parameter Q(6) a maximum was observed at a density rho(t-max) Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(213 citation statements)
references
References 72 publications
11
201
1
Order By: Relevance
“…Analogous behavior has been demonstrated for a similar model. 23 The behavior that we observe in this three-dimensional ͑3D͒ system bears some striking similarities to that observed in two-dimensional system with "repulsive-shoulder" …”
Section: -3supporting
confidence: 51%
“…Analogous behavior has been demonstrated for a similar model. 23 The behavior that we observe in this three-dimensional ͑3D͒ system bears some striking similarities to that observed in two-dimensional system with "repulsive-shoulder" …”
Section: -3supporting
confidence: 51%
“…In these cases, the diffusion coefficient has a region in which it grows with density representing the density anomalous region. The temperature of maximum and minimum diffusion coefficient are lower in the confined system than in the bulk case 69 . Our finding are in agreement with the observations of the diffusion coefficient in coarse-grained model confined between smooth hydrophobic plates, separated at 0.5nm 38 and atomistic models 23 .…”
Section: Systems With Three Layersmentioning
confidence: 98%
“…The pressure versus temperature phase diagram of this system in the bulk was studied by Oliveira et al 68,69 . They found that a system or particles interacting through this potential exhibits a region in the pressure-temperature phase diagram where the density and diffusion coefficient are anomalous.…”
Section: The Modelmentioning
confidence: 99%
“…19,20 Besides these models, effective models have been widely employed in order to study anomalous behavior in bulk water-like systems. [21][22][23][24][25] In these effective models is considered that bulk water form small clusters of four water molecules, and that these clusters come together to form water bicyclo-octamers of different densities. However, in confined systems, these structures are completely different and heavily dependent of the tube geometry and water model employed.…”
Section: Introductionmentioning
confidence: 99%